Measuring endogenous levels of unconjugated bilirubin released from isolated murine brain tissue during oxygen-glucose deprivation - Han-Wei Liu; Ke Lai; Li-Na Gong; Hai-Bo Shi; Shan-Kai Yin; Lu-Yang Wang (STAR Protocols, 2023)
Summary: Quantitative assessment of endogenously synthesized and released bilirubin from brain tissue remains a challenge. Here, we present a sensitive and reproducible experimental paradigm to quantify, in real time, unconjugated bilirubin (UCB) from isolated murine brain tissue during oxygen-glucose deprivation (OGD). We describe steps for perfusion, brain dissection, brain slice preparation and incubation, glucose depletion, and OGD processing. We then detail procedures for standard calibration plotting and sample UCB measurement.For complete details on the use and execution of this protocol, please refer to Liu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.